2020
DOI: 10.1093/pm/pnaa242
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Comparative Trial of Targeted Steroid Injection via Epidural Catheter vs Standard Transforaminal Epidural Injection for the Treatment of Unilateral Cervical Radicular Pain: Six-Month Results

Abstract: Objectives Compare the effectiveness of catheter-directed cervical interlaminar epidural steroid injection (C-CIESI) with triamcinolone to cervical transforaminal steroid injection (CTFESI) with dexamethasone for the treatment of refractory unilateral radicular pain. Design Prospective, randomized, comparative trial. Methods Primary outcome: proportion of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, studies showed no superiority of the targeted catheter approach over a standard C7-T1 IL ESI. Pain relief and other outcome measures were similar at 1 month, 6 months, and 1 year 25–27. The similar efficacy may be secondary to the small epidural space allowing the injectate to flow from C7-T1 to higher cervical levels.…”
Section: Discussionmentioning
confidence: 72%
“…However, studies showed no superiority of the targeted catheter approach over a standard C7-T1 IL ESI. Pain relief and other outcome measures were similar at 1 month, 6 months, and 1 year 25–27. The similar efficacy may be secondary to the small epidural space allowing the injectate to flow from C7-T1 to higher cervical levels.…”
Section: Discussionmentioning
confidence: 72%
“…[ 1 , 4 , 7 , 8 ] CESI may contribute to spinal epidural hematomas and intramedullary cord injections/hematomyelia. [ 2 , 3 , 5 , 6 , 9 ] In this case, the patient’s the MRI-documented intramedullary C3-C6 cystic lesion proved at surgery (i.e. midline myelotomy) to be a chronic intramedullary hematoma.…”
Section: Discussionmentioning
confidence: 89%
“…Medication can also be delivered to the epidural space through an epidural catheter. The rationale for this technique is also to obtain a more ventral and target‐specific administration of medication 74 . With this approach, a soft radiopaque catheter is advanced through an introducer needle to the level and side of pathology with the final position of the catheter tip located in either the posterior epidural space or in the lateral recess close to the site of the inflamed spinal nerve.…”
Section: Treatmentsmentioning
confidence: 99%
“…The rationale for this technique is also to obtain a more ventral and target-specific administration of medication. 74 With this approach, a soft radiopaque catheter is advanced through an introducer needle to the level and side of pathology with the final position of the catheter tip located in either the posterior epidural space or in the lateral recess close to the site of the inflamed spinal nerve. One RCT demonstrated that a catheter-directed interlaminar CESI was as effective as a transforaminal CESI in reducing pain and disability in patients with refractory unilateral cervical radicular pain for up to 1 year.…”
Section: Interventional Pain Managementmentioning
confidence: 99%